Fused silica capillaries with two segments of different internal diameters and inner surface roughnesses prepared by etching with supercritical water and used for volume coupling electrophoresis. Issue 9 (16th March 2017) - Horká, Marie; Karásek, Pavel; Roth, Michal; Šlais, Karel
Abstract : In this work, single‐piece fused silica capillaries with two different internal diameter segments featuring different inner surface roughness were prepared by new etching technology with supercritical water and used for volume coupling electrophoresis. The concept of separation and online pre‐concentration of analytes in high conductivity matrix is based on the online large‐volume sample pre‐concentration by the combination of transient isotachophoretic stacking and sweeping of charged proteins in micellar electrokinetic chromatography using non‐ionogenic surfactant. The modified surface roughness step helped to the significant narrowing of the zones of examined analytes. The sweeping and separating steps were accomplished simultaneously by the use of phosphate buffer (pH 7) containing ethanol, non‐ionogenic surfactant Brij 35, and polyethylene glycol (PEG 10000) after sample injection. Sample solution of a large volume (maximum 3.7 μL) dissolved in physiological saline solution was injected into the wider end of capillary with inlet inner diameter from 150, 185 or 218 μm. The calibration plots were linear ( R 2 ∼ 0.9993) over a 0.060–1 μg/mL range for the proteins used, albumin and cytochrome c. The peak area RSDs from at least 20 independent measuremens were below 3.2%. This online pre‐concentration technique produced a more than 196‐fold increase in sensitivity, and it can be applied for detection of, e.g . the presence of albumin in urine (0.060 μg/mL).